New species of Anillinus Casey (Carabidae: Trechinae: Bembidiini) from Great Smoky Mountains National Park, U.S.A. and phylogeography of the A. langdoni species group - Sokolov, Igor M.; Sokolova, Yuliya Y.; Carlton, Christopher E. (Zootaxa, 2007)
The Anillinus langdoni–species group is characterized and two new species are described, Anillinus cieglerae Sokolov and Carlton sp. nov. and A. pusillus Sokolov and Carlton sp. nov., both from Great Smoky Mountains National Park. The langdoni–group includes four species at present, three apparently endemic to the Great Smoky Mountains and adjacent mountains of western North Carolina/Tennessee, and a fourth from South Mountains of middle North Carolina. They are distinguished mainly using characters of the male genitalia and to a lesser extent, differences in shapes of female spermathecae. Phylogenetic analyses based on aedeagal morphology and COI gene sequences yielded conflicting results, with the later providing a phylogeny that was more parsimonious with expectations based on geographic distributions. Speciation within the group may derive from ecological constraints and altitudinal fluctuations of habitat corridors during past climate changes combined with the impact of local watersheds as fine scale isolating mechanisms.